2019
DOI: 10.1002/pts.2477
|View full text |Cite
|
Sign up to set email alerts
|

Are cellulose nanocrystals “alien particles” to human experience?

Abstract: A wide family of cellulose‐based additives are authorized worldwide as fillers and thickening agents in foods, pills, and tablets, and microcrystalline cellulose (MCC) is, among these, the most important one. Since MCC manufacturing is similar to the main production route of cellulose nanocrystals (CNCs), it is reasonable to wonder whether the MCC would contain CNCs as minor components. In this Short Communication, we provide first results about the occurrence of CNCs in MCC, observed by dynamic light scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A recent work demonstrated that cellulose nanoparticles have always been part of our daily intake. The findings provided further necessary and preliminary information/data to the EFSA for the approval of the cellulose nanoparticles as FCMs [116]. Although studies have shown that, for 10 nm diameter particles, an apparent diffusion coefficient (D) of 1.1 × 10 −35 cm 2 s −1 theoretically calculated in a LDPE host matrix exhibits a benign risk of inadvertent migration [117], it remains that the same investigation has to be performed specifically on CNCs to confirm those results.…”
Section: Regulations About Cncs and Mfc/cnfsmentioning
confidence: 81%
“…A recent work demonstrated that cellulose nanoparticles have always been part of our daily intake. The findings provided further necessary and preliminary information/data to the EFSA for the approval of the cellulose nanoparticles as FCMs [116]. Although studies have shown that, for 10 nm diameter particles, an apparent diffusion coefficient (D) of 1.1 × 10 −35 cm 2 s −1 theoretically calculated in a LDPE host matrix exhibits a benign risk of inadvertent migration [117], it remains that the same investigation has to be performed specifically on CNCs to confirm those results.…”
Section: Regulations About Cncs and Mfc/cnfsmentioning
confidence: 81%
“…It should be noted that the approval of cellulose nanocrystals to be used as food contact materials (FCMs) is still under evaluation in Europe, although recent studies are being taken into account by the EFSA for their positive assessment (Fotie, Limbo, & Piergiovanni, 2020;Piergiovanni, Fotie, Amoroso, Akgun, & Limbo, 2019). However, other countries like Canada have recently unrestricted the commercialization and use of cellulose nanocrystals, according to their lack of toxicity as observed by several regulatory protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of applications of CNMs in food technology or biomedical applications are still in the early R&D stages, but they are expected to reach the market in the near future. Nevertheless, as recently suggested, CNMs-and particularly CNCs-might already be present in many food products and pharmaceuticals [118]. Studies have suggested that CNCs may represent a small fraction of the particles present, for example, in microcrystalline cellulose (MCC)-a typical food and drug additive that is considered to be safe.…”
Section: Cnms In Food Technology and Biomedicinementioning
confidence: 99%
“…Studies have suggested that CNCs may represent a small fraction of the particles present, for example, in microcrystalline cellulose (MCC)-a typical food and drug additive that is considered to be safe. This observation was based on a preliminary study, in which particles with diameter/width less than 100 nm were found after serial filtration of MCC suspensions [118]. However, the presence of CNMs in food/food packaging products or pharmaceutical/nutraceutical drugs is currently largely unknown.…”
Section: Cnms In Food Technology and Biomedicinementioning
confidence: 99%